ANALISIS KEUNTUNGAN INDUSTRI ROTAN DI KOTA JAYAPURA PROVINSI PAPUA - Wambrauw, Yustina Lina Dina (Department of Social Economic Agriculture, Faculty of Agriculture, University of Papua, Manokwari, West Papua, Indonesia, 2015)
Economic development are described of Increasing of inventions. As a developed country many people make use harvest of forest and agriculture to get income from them. Papua has many business that use harvest of forest and agriculture for example rattan business. Research was conducted in Jayapura city by using descriptive methods with case study. Case that was acknowledged in this study are three industries of rattan that are registered in Departemen Perindustrian Perdagangan dan Koperasi (DEPERINDAKOP). Primary and secondary data were collected by direct interviews and from some instances. The results show that the average of invention of rattan industries in Jayapura city is 72.509.743, 3 per year. The business can give profit for rattan industry and generally can give contributions for development of economy in Papua.